Formação de um banco ativo de germoplasma, seleção de acessos e propagação vegetativa de Bougainvillea - Foschini, Jessica (Universidade Federal de São Carlos, 2017)
The world market of flowers and ornamental plants have been demonstrating high growth along the last years. Accompanying this growth, it is also observed the increase of the interest by the study and production of new species with potential of ornamental use, among them the primavera (Bougainvillea sp.), a gender with many native species of Brazil. The cultivation and the production of primavera in vases in Brazil are a recent practice, and he has as need the development of technologies that they make possible the process, as the choice of appropriate genotypes, the propagation, floral induction and durability of the flowers. In that context, the selection of more appropriate genotypes to the cultivation in vase with herbaceous characteristics and semi-shrub, as well as the effectiveness of technology of vegetative propagation for maintenance of the production are primordial in the productive process. Being like this, this work had as objectives: (1) formation of an Active Bank of Germplasm seeking to the selection of accesses and futures programs of genetic improvement and propagation; (2) establishment in vitro of commercial accesses of primavera using different explants and culture means; (3) multiplication of cuttings and rooting vegetation home for the cutting technique. To the total they were collected and identified ten accesses for formation of BAG, of which two were used for studies of vegetative propagation, being just an used in the study in vitro (A1. B. glabra). In function of the obtained results, it can be said that the primavera cultivation in vitro can come to be an alternative for production of the species being used as explant stem apexes, asepsis in sodium hypochlorite 60% for 20 and a half minutes of cultivation WPM, however the established protocols in that study still don't allow the production of seedlings in laboratory. Already the technique of stem cutting was shown viable for obtaining of seedlings, could be applied to a commercial cultivation. The best results presented for stem cutting were with the use of AIB in the concentration of 1000 ppm for the access A5 (B. spectabillis), and without auxin addition for the access A1 (B. glabra).
Formation of active germplasm bank, selection of access and vegetative propagation of Bougainvillea
Keywords: Banco de germoplasma; cultura de tecidos; Bougainvillea; produção de flores; CIENCIAS AGRARIAS::AGRONOMIA